Direct Structure–Performance Comparison of All‐Carbon Potassium and Sodium Ion Capacitors. Issue 12 (24th April 2019) - Xu, Ziqiang; Wu, Mengqiang; Chen, Zhi; Chen, Cheng; Yang, Jian; Feng, Tingting; Paek, Eunsu; Mitlin, David
Abstract: A hybrid ion capacitor (HIC) based on potassium ions (K + ) is a new high‐power intermediate energy device that may occupy a unique position on the Ragone chart space. Here, a direct performance comparison of a potassium ion capacitor (KIC) versus the better‐known sodium ion capacitor is provided. Tests are performed with an asymmetric architecture based on bulk ion insertion, partially ordered, dense carbon anode (hard carbon, HC) opposing N‐ and O‐rich ion adsorption, high surface area, cathode (activated carbon, AC). A classical symmetric "supercapacitor‐like" configuration AC–AC is analyzed in parallel. For asymmetric K‐based HC–AC devices, there are significant high‐rate limitations associated with ion insertion into the anode, making it much inferior to Na‐based HC–AC devices. A much larger charge–discharge hysteresis (overpotential), more than an order of magnitude higher impedance R SEI, and much worse cyclability are observed. However, K‐based AC–AC devices obtained on‐par energy, power, and cyclability with their Na counterpart. Therefore, while KICs are extremely scientifically interesting, more work is needed to tailor the structure of "Na‐inherited" dense carbon anodes and electrolytes for satisfactory K ion insertion. Conversely, it should be possible to utilize many existing high surface area adsorption carbons for fast rate K application. Abstract : A hard carbon ion insertion anode gives much higher overpotential with K + versus Na + . This significantly lowers the energy and power of symmetric hybrid potassium ion capacitor (KIC) versus sodium ion capacitor. However, high surface area ion adsorption carbon works well with both K and Na, opening the possibility for high‐performance symmetric KICs.